Penggunaan Strategi Reconnecting pada Materi Penciptaan Manusia bagi Siswi Kelas XI MA Nurul Hasan Probolinggo - Muniro Muniro; Herwati Herwati; Ainol Ainol (Edudeena : Journal of Islamic Religious Education, 2022)
Abstract: This classroom action research (CAR) is applied face to face using the Reconnecting strategy. This strategy departs from students who very often not focus when learning so they not understand the subject matter. This study aims to improve understanding of the material of human creation and its essence in class XI MA Nurul Hasan. The sample studied amounted to 16 students. The data collection techniques are observation and tests in 2 cycles. Each cycle has 2 meetings consisting of planning, action, observation and evaluation. The three aspects of student understanding in this study were reexplaining, giving examples and answering questions. The success rate of the “reexplaining” aspects in the first cycle of the first meeting reached 3,7 percent and the second meeting reached 4,3 percent. Furthermore, in the second cycle the first meeting reached 4,8percent and the second meeting reached 5 percent. The success rate of the “giving examples” aspects in the first cycle of the first meeting reached 4,5 percent and the second meeting reached 4,9 percent. Furthermore, in the second cycle the first meeting reached 5,1 percent and the second meeting reached 5,3 percent. The success rate of the “answering questions” aspects in the first cycle of the first meeting reached 4,5 percent and the second meeting reached 4,7 percent. Furthermore, in the second cycle the first meeting reached 4,9 percent and the second meeting reached 5,2 percent. This matter that the Reconnecting strategy is effective as effort to understand the learning of the Quran Hadith. Abstrak: Penelitian tindakan kelas (PTK) ini diterapkan secara tatap muka dengan menggunakan strategi Reconnecting. Strategi ini berangkat dari para siswa yang sangat sering tidak fokus ketika pembelajaran sehingga tidak memahami materi pelajaran. Penelitian ini bertujuan untuk meningkatkan pemahaman materi penciptaan manusia dan hakikatnya pada siswi kelas XI MA Nurul Hasan. Sampel yang diteliti berjumlah 16 siswa. Adapun teknik pengumpulan data yaitu observasi dan tes dalam 2 siklus. Setiap siklusnya mempunyai 2 pertemuan terdiri dari perencanaan, tindakan, pengamatan dan evaluasi. Tiga aspek pemahaman siswa dalam penelitian ini adalah menjelaskan kembali, memberikan contoh dan menjawab soal. Tingkat keberhasilan aspek “menjelaskan kembali” pada siklus I pertemuan pertama mencapai 3,7 persen dan pertemuan kedua mencapai 4,3 persen. Selanjutnya pada siklus II pertemuan pertama mencapai 4,8 persen dan pertemuan kedua mencapai 5 persen. Tingkat keberhasilan aspek “memberikan contoh” pada siklus I pertemuan pertama mencapai 4,5 persen dan pertemuan kedua mencapai 4,9 persen. Selanjutnya pada siklus II pertemuannpertama mencapai 5,1persen dan pertemuan kedua mencapai 5,3 persen. Tingkat keberhasilan aspek “menjawab soal” pada siklus I pertemuan pertama mencapai 4,5 persen dan pertemuan kedua mencapai 4,7 persen. Selanjutnya pada siklus II pertemuan pertama mencapai 4,9 persen dan pertemuan kedua mencapai 5,2 persen. Hal ini menunjukkan bahwa strategi Reconnecting efektif dalam upaya memahami pembelajaran al-Quran Hadis.